PROSES KOMUNIKASI INTERPERSONAL PEMBINA DALAM MENGUBAH PERILAKU WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KELAS II B ANAK PEKANBARU - Andini, Tamira Dwi; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Delinquency and crime among children and adolescents continues to increase in fact lead to acts classified as crimes . To restore the attitudes and behavior of children and adolescents is needed coaching . One container of coaching for children and adolescents are prisons . The development occurred in the communication is a tool to change the behavior of children and adolescents . This study to know how the desire of communication between supervisors and inmates , the message delivered between supervisors and inmates , sending messages between supervisors and inmates , receiving messages between supervisors and inmates , understanding messages between supervisors and inmates , as well as feedback between supervisors and inmates in correctional facilities and child class II Pekanbaru The design of this research was used descriptive qualitative method which is explaining and interpreting the data that have already existed. The informants of this research are the cultivator and the cultivate society by using the purposive technique. The technique of data collection has done by using observation, interview, and documentation. The result of this research was showed the process of interpersonal communication thathave done by cultivator and the cultivate society that prove that it can be running well at Correctional Institution of II B Class of Protégé in Pekanbaru. Moreover, the desire of communication between the cultivator and the cultivate society can be fulfilled to each other. The message that will be delivered by cultivator and the cultivate society should be aimed to personal problem so that one of the side can feel comfortable to share what they feel. The sending messages that have done by cultivator and cultivate society were doing directly or face to face where the messages that have been sending will be delivered directly. The delivering message that have done by cultivator and cultivate society is still running well, in addition the cultivate society are very enthusiastic when they join the agendas that held by Correctional Intuition, as well as on the other way, so that the cultivate society can be assimilated to another. The understanding of cultivator and cultivate society have well enough where the cultivate society can be understood what the cultivator has communicated, as well as on the other way. Keyword : communication process of interpersonal, builder, institution of II B class of Protage